2022
DOI: 10.3390/ijms23063116
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analyses of Four PtoNF-YC Genes from Populus tomentosa and Impacts on Flowering Timing

Abstract: Flowering is an important link in the life process of angiosperms, and it is also an important sign of the transformation of plants from vegetative to reproductive growth. Although the flowering regulation network of Arabidopsis is well-understood, there has been little research on the molecular mechanisms of perennial woody plant flower development regulation. Populus tomentosa is a unique Chinese poplar species with fast growth, strong ecological adaptability, and a long lifecycle. However, it has a long juv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…As a transcription factor (TF) that regulates plant growth and stress resistance, the NF-Y has been identified and studied in multiple plants. There were 36 NF-Ys in A. thaliana (Siefers et al, 2009), 25 NF-Ys in Ricinus communi (Wang et al, 2018), 59 NF-Ys in Solanum lycopersicum , 32 NF-Ys in Vitis vinifera (Ren et al, 2016), 33 NF-Ys in Juglans regia (Quan et al, 2018), 24 NF-Ys in peach (Li et al, 2019), 28 NF-Ys in Pinus tabuliformis (Guo et al, 2020), 52 NF-Ys in P. trichocarpa (Liu et al, 2021), and 46 NF-Ys in P. tomentosa (Li et al, 2022). In this study, a total of 26 NF-Y members were cloned in P. davidiana × P. bollena, including 12 PdbNF-YAs, six PdbNF-YBs, and eight PdbNF-YCs (Table 1, Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…As a transcription factor (TF) that regulates plant growth and stress resistance, the NF-Y has been identified and studied in multiple plants. There were 36 NF-Ys in A. thaliana (Siefers et al, 2009), 25 NF-Ys in Ricinus communi (Wang et al, 2018), 59 NF-Ys in Solanum lycopersicum , 32 NF-Ys in Vitis vinifera (Ren et al, 2016), 33 NF-Ys in Juglans regia (Quan et al, 2018), 24 NF-Ys in peach (Li et al, 2019), 28 NF-Ys in Pinus tabuliformis (Guo et al, 2020), 52 NF-Ys in P. trichocarpa (Liu et al, 2021), and 46 NF-Ys in P. tomentosa (Li et al, 2022). In this study, a total of 26 NF-Y members were cloned in P. davidiana × P. bollena, including 12 PdbNF-YAs, six PdbNF-YBs, and eight PdbNF-YCs (Table 1, Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…It was first reported in Arabidopsis that NF-YC played a critical role in the photoperiodic pathway by interacting directly with CONSTANS (CO) [ 20 , 22 ]. Subsequently, the involvement of NF-YC in the photoperiodic flowering response was reported in rice [ 21 ], maize [ 25 ], poplar [ 23 ], and other plants. Recent studies have shown that the regulation of flowering by NF-Y family members may also be related to the GA and age pathway [ 7 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear Factor Y, Subunit C (NF-YC), also known as Histone-Associated Protein 5 (HAP5) or CCAAT Binding Factor C (CBF-C), is a subunit of NF-Y trimers [ 19 ]. The NF-YC gene family is considered to participate in flowering time regulation [ 7 , 20 , 21 , 22 , 23 , 24 ]. In Arabidopsis , NF–YC3, NF–YC4, and NF–YC9 have high amino acid identity.…”
Section: Introductionmentioning
confidence: 99%
“…The research from databases indicate, that the use of poplar species in urban greenery initiatives, including e.g. P. tomentosa, P.s alba 'Berolinensis', and P. nigra, is driven by their rapid growth, strong adaptability, and tolerance to environmental stressors [121,122,123]. These species are favored for their ability to thrive in diverse urban settings, offering benefits such as flood tolerance and resilience to adverse conditions [124,125].…”
Section: The Fast Increments Of Poplarsmentioning
confidence: 99%
“…Populus tomentosa exhibits rapid growth and ecological adaptability, making it ideal for establishing greenery in urban areas [121]. Similarly, the hybrid triploid P. alba 'Berolinensis' demonstrates fast growth and high stress tolerance, suitable for urban forestry [122].…”
Section: The Fast Increments Of Poplarsmentioning
confidence: 99%